Estrogens in Human Male Gonadotropin Secretion and Testicular Physiology From Infancy to Late Puberty - Guercio, Gabriela; Saraco, Nora; Costanzo, Mariana; Marino, Roxana; Ramirez, Pablo; Berensztein, Esperanza; Rivarola, Marco A.; Belgorosky, Alicia (Frontiers in Endocrinology, 2020)
Several reports in humans as well as transgenic mouse models have shown that estrogens play an important role in male reproduction and fertility Estrogen receptor alpha (ERα) and beta (ERβ) are expressed in different male tissues including the brain. The estradiol-binding proteinGPER1also mediates estrogen action in target tissues. In human testes a minimal ERα expression during prepuberty along with a marked pubertal up-regulation in germ cells has been reported. ERβ expression was detected mostly in spermatogonia, primary spermatocytes, and immature spermatids. In Sertoli cells ERβ expression increases with age. The aromatase enzyme (cP450arom), which converts androgens to estrogens, is widely expressed in human tissues (including gonads and hypothalamus), even during fetal life, suggesting that estrogens are also involved in human fetal physiology. Moreover, cP450arom is expressed in the early postnatal testicular Leydig cells and spermatogonia. Even though the aromatase complex is required for estrogen synthesis, its biological relevance is also related to the regulation of the balance between androgens and estrogens in different tissues. Knockout mouse models of aromatase (ArKO) and estrogen receptors (ERKOα, ERKOβ, and ERKOαβ) provide an important tool to study the effects of estrogens on the male reproductive physiology including the gonadal axis. High basal serum FSH levels were reported in adult aromatase-deficient men, suggesting that estrogens are involved in the negative regulatory gonadotropin feedback. However, normal serum gonadotropin levels were observed in an aromatase-deficient boy, suggesting a maturational pattern role of estrogen in the regulation of gonadotropin secretion. Nevertheless, the role of estrogens in primate testis development and function is controversial and poorly understood. This review addresses the role of estrogens in gonadotropin secretion and testicular physiology in male human sespecially during childhood and puberty.